Mito‐docking: A Novel In Vivo Method to Detect Protein–Protein Interactions. Issue 10 (11th June 2019) - Shao, Wei; He, Lihong; Deng, Fei; Wang, Hualin; Vlak, Just M.; Hu, Zhihong; Wang, Manli
Abstract: Many methods have been developed to detect protein–protein interactions (PPIs) and explore cellular processes. However, effective methods for detecting complicated PPIs under physical conditions are still in demand. Here, a simple and efficient mitochondria‐docking (Mito‐docking) method for PPI detection in vivo is developed. The strategy is to anchor a "bait" protein to mitochondrial outer membrane (MOM), and then trap the "prey" protein onto MOM. In this way, interacting signals are enriched to allow easy detection. This method efficiently detects the well‐known interaction between two G protein subunits (Gγ2 with Gβ1 ) and is successfully applied to investigate the recognition of importin α superfamily members for the classical nuclear localization signal (NLS) of simian virus 40 (SV40) large T antigen, which are highly dynamic and not easily visualized by conventional methods. As far as is known, this is the first time that the interaction between human importin α receptors with NLSs has been visualized. The results prove that Mito‐docking can be used as a simple, straightforward, and intuitive method to study PPIs qualitatively and quantitatively in vivo. Abstract : Mito‐docking is a simple and effective method to detect protein–protein interactions (PPIs) in vivo. The strategy anchors a ''bait" protein (A) onto mitochondrial outer membrane (MOM) and traps ''prey" proteins (B) onto MOM, thus, genuine PPIs can be shown by the relocation and enrichment of the prey proteins on MOM. This method allows detecting or even quantifying dynamic PPIs.